Effectiveness of Sofosbuvir and Velpatasvir Combination in Chronic Hapatitis C - Agha Wali, Ghulam Hassan, Sohail Hussain, Muhammad Naeem Aslam, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to evaluate the efficacy of a combination medication consisting of sofosbuvir and velpatasvir in treating individuals with chronic hepatitis C. Study Design: Observational/ Prospective study Place and Duration: Conducted at Department of Gastroenterology Mayo Hospital Lahore, during from the period Feb 2021 to Jan 2022. Methods: There were 67 participants in this study. The patients' ages ranged from 18 to 70. We gathered demographic information about the patient, such as age, gender, height, and weight, after getting written consent. Hepatitis C patients with known genotypes were shown. A SOF/VLP regimen containing sofosbuvir and velpatasvir was administered to patients for a total of 12 weeks. The entire set of data was examined using SPSS 18.0. Results: In current study, 42 (62.7%) were males and 25 (37.3%). Included patients had mean age 31.12±15.80 years and mean BMI 24.7±8.34 kg/m2. We found that efficacy rate was higher and found in 63 (94.03%) cases. As per laboratory findings, aspartate aminotransferase (AST) 37.5± 11.21, alanine aminotransferase (ALT) 26.2±6.44, and haemoglobin level 12.24±10.17 all showed considerable improvement after therapy. Most common adverse outcomes were headache 35 (52.2%), fatigue 22 (32.8%) and nausea 10 (14.9%). Conclusion: In patients with or without cirrhosis, and regardless of the HCV genotype, the combination of sofosbuvir and velpatasvir has shown to be extremely successful in treating chronic HCV infection. This is true regardless of the HCV genotype. Keywords:, Hepatitis C, Sofosbuvir, Comorbidities, Velpatasvir,